2003
DOI: 10.1259/dmfr/92201340
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of static bone cavities with CT and MRI

Abstract: Examination of contrast-enhanced CT images and MR images revealed that the contents of SBCs were not aberrations of the submandibular gland, as has generally been thought, but fatty tissue, blood vessels and soft tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0
13

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 16 publications
2
55
0
13
Order By: Relevance
“…SBD was described by most authors as static and patient's age on detection was usually in excess of 20 years, most often in the fifth and sixth decades. 6,9,15 The 12 SBDs reported by Minowa et al 8 were in patients aged 18-64 years (mean age 57 years). Our sample shows a predominance of patients diagnosed between 40 years and 70 years of age.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…SBD was described by most authors as static and patient's age on detection was usually in excess of 20 years, most often in the fifth and sixth decades. 6,9,15 The 12 SBDs reported by Minowa et al 8 were in patients aged 18-64 years (mean age 57 years). Our sample shows a predominance of patients diagnosed between 40 years and 70 years of age.…”
Section: Discussionmentioning
confidence: 96%
“…However, they did not suggest any possible cause for the ischaemia. In recent times, Minowa et al 7,8,22 suggested that bone erosion due to an acquired vascular lesion is another possible explanation for the formation of SBD of the mandible. According to them, the facial artery and its branches can become tortuous owing to hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the number of reports continues to accumulate, knowledge about the aetiology and pathogenesis of SBD has been limited and confusing for a long time. 3,[7][8][9][10] Although the radiological features of SBD have been widely reported, the use of cone beam CT (CBCT) for its diagnosis has been rarely reported. 11 The aim of this article is to clarify the frequency of this phenomenon by using multi-slice CT (MSCT) and CBCT to add to our understanding of the aetiology and content of SBDs by MSCT analysis, and to investigate CBCT use as a tool for exploring SBDs…”
Section: Introductionmentioning
confidence: 99%